KEMISKINAN DI DAERAH KAYA SUMBERDAYA ALAM, SEBUAH PARADOKS PEMBANGUNAN - Ahmad Zaini (Puslatbang KDOD Lembaga Administrasi Negara, 2010)
Poverty is a problem which always appear in each economy. Whom live in the poverty is the victim from economy system which unbiased in their limitation. During the time economy system tend pay attention to the economy growth compared with result redistributing of development, so the wide of disparity become progressively. In fact, both of the other is not interfere in, exactly it contrary strengthening each other. Economy growth can be done at the same time with result of redistributing development. Here, government is the important roles, with their policy, government can be redistribute result of economy growth so it can be prosperous all the people in the region. The region with have own resources, really have larger opportunity than other region to decrease the poverty. With that properties, government can make a lot of programs to decrease the poverty. But the history indicate that a lot of states which have not resources get better prosperity than state which rich of resources. The management of resource is the key, if truly managed will become benediction, but if not truly managed it will become curses. Keywords : poverty, economy growth, resources